(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
Almost all of the speech intelligibility (SI) assessors today are from the West. The words used in the development of these SI assessors are mainly English. However, recent finding has found that word components that contribute to intelligibility of speech is different from one language to another. The purpose of this study is to determine Bahasa Melayu (BM) word list from Friday sermon transcripts. The project was undertaken by deriving BM words spoken during 52 Friday sermons read in mosques in Wilayah Persekutuan Kuala Lumpur. PHP is the programming language used to compute the frequency of words appears in the Friday sermon transcripts. These words were then stored into a database. The database used is MySQL. It has been found that the highest number of repeated word is 2509. The list is then truncated so that the numbers of repeated words range from 52 to 2509 times. The frequency of Bahasa Melayu words used in Friday sermons is an initial and important inventory that can be used in the development of SI assessor using BM words.